Combined cerebral atrophy score in Huntington's disease based on atlas-based MRI volumetry: Sample size calculations for clinical trials - Müller, Hans-Peter; Huppertz, Hans-Jürgen; Dreyhaupt, Jens; Ludolph, Albert C.; Tabrizi, Sarah J.; Roos, Raymund A.C.; Durr, Alexandra; Landwehrmeyer, G. Bernhard; Kassubek, Jan (Parkinsonism & related disorders, 2019)
A volumetric MRI analysis of longitudinal regional cerebral atrophy in Huntington's disease (HD) was performed as a read-out of disease progression to calculate sample sizes for future clinical trials. This study was based on MRI data of 59 patients with HD and 40 controls recruited within the framework of the PADDINGTON study and investigated at baseline and follow-up after 6 and 15 months. Automatic atlas-based volumetry (ABV) of structural T1-weighted scans was used to calculate longitudinal volume changes of brain structures relevant in HD and to assess standardized effect sizes and sample sizes required for potential future studies. Atrophy rates were largest in the caudate (−3.4%), putamen (−2.8%), nucleus accumbens (−1.6%), and the parietal lobes (−1.7%); the lateral ventricles showed an expansion by 6.0%. Corresponding effect sizes were −1.35 (caudate), −0.84 (putamen), −0.91 (nucleus accumbens), −1.05 (parietal lobe), and 0.92 (lateral ventricles) leading to N = 36 subjects per study group for detecting a 50% attenuation of atrophy for the best performing structure (caudate). A combined score of volume changes in non-overlapping compartments (striatum, parietal lobes, lateral ventricles) increased the effect size to −1.60 and substantially reduced the required sample sizes by 10 to N = 26 subjects per study group. This combined imaging score correlated significantly both with the CAP score and with the progression of the clinical phenotype. We propose ABV of the striatum together with parietal lobe and lateral ventricle volumes as a combined imaging read-out for progression studies including clinical trials in HD. •Atlas-based volumetry (ABV) is proposed as imaging read-out for progression in HD.•A combined volumetric score resulted in an effect size of −1.60.•ABV is a candidate for clinical trials to detect therapeutic efficacy in HD.